Measuring Relative Sustainability of Regions Using Regional Sustainability Assessment Methodology. Issue 4 (18th April 2016) - Smetana, Sergiy; Tamásy, Christine; Mathys, Alexander; Heinz, Volker
Abstract : Scientists analyze sustainability at the regional level with a combination of multiple indicators which reflect different characteristics of regions without combining the results in a single comparative unit. Moreover, the assessment of interdependencies between different characteristics requires experts' analyses, which makes sustainability analysis subjective, time consuming, and limited in use. This article analyzes the relative sustainability of subnational level regions through the application of regional sustainability assessment methodology (RSAM) based on accounting of resources capital and its internal and external transfers. This approach allows for assessment of regional sustainability as a function of resource quantity, quality, and interchangeability. The comparison of the two case study regions presented in the paper indicates the difference between a more sustainable region and a region of "weak sustainability." First, the article indicates the discussion of the relevant geographic, economic, and social literature for both sustainability assessment and regional comparison. This discussion is followed by a conceptual representation of proposed RSAM and its application to various regions. Next, the article covers the data used and applied methods to test the proposed methodology and compare the two case study regions. The article concludes with a discussion of findings and recommendations for further application and testing.